The metabolomic approach to the comparative analysis of wild and cultivated species of oats (Avena L.) - I. G. Loskutov; T. V. Shelenga; A. V. Konarev; A. I. Shavarda; E. V. Blinova; N. I. Dzubenko (Вавиловский журнал генетики и селекции)
Seed metabolomic profiles have been investigated in wild and cultivated forms (cultivars) of oat (Avena L.). Seed accessions from the VIR oat collection were used for the research. Metabolomic analysis employed gas liquid chromatography-mass spectrometry (GLC- MS) using an Agilent 6850 chromatographer (USA). The analysis covered the composition and content of organic and fatty acids, amino acids, polyatomic spirits and sugars. The content fluctuation range for the studied groups of compounds was found to be narrower (significantly in some cases) in cultivars than in the wild species. Along with a sharp increase in oleic acid content, cultivars demonstrated a decrease in that of linoleic acid. The general conclusions from the comparison of seed metabolomic profiles in wild species and cultivars are presented below. A number of wild species can be recommended as a potential source of biochemical quality traits for breeding purposes. A series of metabolites (compounds), the content of which changes during domestication or which differentiate wild oat species from cultivars has been identified was found. Along with such well-known healthy food chemical factors as oleic acid, glucose and fructose, etc., differences concerning monoacylglycerol compounds (MAG 16 : 0 and MAG-2 18 : 2, etc.) have been found. The latter have been proposed to be related to the formation of adaptive traits, in particular, resistance to diseases and pests, and to environmental abiotic stresses.